2021
DOI: 10.1136/postgradmedj-2020-139631
|View full text |Cite
|
Sign up to set email alerts
|

Effect of serial awake prone positioning on oxygenation in patients admitted to intensive care with COVID-19

Abstract: IntroductionAwake prone positioning (APP) might benefit patients with COVID-19 by improving oxygenation, but it is unknown whether this improvement can be sustained with serial proning episodes.MethodsWe conducted a retrospective review of adults with COVID-19 admitted to one intensive care unit, in those who underwent APP and controls. Patients in both groups had type 1 respiratory failure requiring oxygen (but not initially intubated), confirmed SARS-CoV-2 PCR by nasopharyngeal swab and findings of multifoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…In addition, there was lower rate of intubation in patients with an Spo2 of 95% or greater after 1 hour of the prone position. 10 The present study also shows significant improvement on respiratory rate which was further supported by Sartini C et al (2020) concluded that compared to baseline the respiratory rate was lower and the oxygenation was higher during and after pronation. 11 Thus the present study concluded that Positioning exercises can be considered as an effective method for better improvement by relieving dyspnea and fatigue in COVID 19 treated in addition to the regular medical treatment.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, there was lower rate of intubation in patients with an Spo2 of 95% or greater after 1 hour of the prone position. 10 The present study also shows significant improvement on respiratory rate which was further supported by Sartini C et al (2020) concluded that compared to baseline the respiratory rate was lower and the oxygenation was higher during and after pronation. 11 Thus the present study concluded that Positioning exercises can be considered as an effective method for better improvement by relieving dyspnea and fatigue in COVID 19 treated in addition to the regular medical treatment.…”
Section: Discussionsupporting
confidence: 87%
“…After the search of the literature, 99 records were retrieved, of which only 9 studies [ 10 12 , 19 24 ] were observational comparison-group studies including both AP and supine patients, with sufficient information to calculate the overall risk of intubation, which are summarised alongside the APRONOX study in figure 3 ; the funnel plot is provided as Appendix 9 .…”
Section: Resultsmentioning
confidence: 99%
“…Early case series studies have shown a reduction of respiratory rate and improvement in SpO 2 , PaO 2 , and PaO 2 :FIO 2 during APP, [ 8 , 9 ] which have been confirmed by subsequent cohort studies. [10] , [11] , [12] , [13] , [14] This improvement in oxygenation and clinical presentation usually happens in the early stage of APP (from 30 min to 6 h) of the first episode. However, several observational studies have reported no improvement in oxygenation after APP.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 , 29 ] Efforts have been undertaken to reduce the need for intubation due to its association with higher mortality and the use of scarce resources in the pandemic setting. [ 2 , 7 ] Early observational studies have shown controversial effects of APP on the need for intubation, [ [10] , [11] , [12] , [13] , [14] , [15] , [16] , [30] , [31] , [32] ] while early randomized controlled studies with small sample sizes have not been able to detect the differences in intubation by APP. [ [17] , [18] , [19] , [20] , 33 ] However, from observational studies, it is interesting to note that a significant reduction in the need for intubation through APP implementation has been found in most of the studies in which patients received predominantly high-flow nasal cannula (HFNC).…”
Section: Introductionmentioning
confidence: 99%